Rancang Bangun Pillbox dengan Fitur Pengingat Minum Obat - Siswanto, Putri Alief; Safira, Laily Asna; Jafari, Nadya Paramitha; Pramanasari, Indra; Al Zulmi, Kahlil Gibran; Ramadhani, Annisa Azzahra; Fitria, Nadia Salmah; Azmina, Tanaya Hannani Nur; Luthfia, Ranaya Talitha; Mubarak, Abdurrahman; Reawaruw, Timothy Manulus (Jayapangus Press, 2025)
The increasing prevalence of chronic illness, which requires long-term therapy, indicates the need for a medication reminder system. The Pillbox prototype was built using a design thinking approach (empathize, define, ideate, prototype, and test). Interview results during the empathize phase revealed difficulties in managing multiple medications with varying dosing schedules without a reminder system. The define phase identified that existing pillboxes had inadequate compartments and no reminder systems featured. The ideate phase proposed a solution to design a pillbox with specific dimensions and configurations to accommodate diverse medication types and integrate an audiovisual reminder system. During the prototype phase, development proceeded through the planning of design and electronic systems, featuring a buzzer for alarms, LED lights as visual indicators, mechanical end-stop sensors for lid detection, a Nextion touchscreen interface for time settings, and an Arduino Nano microcontroller for computational and control functions. The test phase involved nine trials. Alarm time accuracy, measured by the difference between alarm activation and setting times, demonstrated good results at 29.22 ± 14.57 seconds. LED lights and sensor responsivity performed well across all trials. Functional testing demonstrated satisfactory performance. A pillbox prototype with an audiovisual reminder feature is designed to increase medication adherence rates.